An organization design redefinition for the tourism sector using design thinking: Sustainable hotels case study - Lamelas, D.; Lamelas, J. P.; Filipe, J. (Modeling and new trends in tourism: A contribution to social and economic development, 2017)
This chapter shows how the Classic Design Theory may be applied to create a new philosophy for organizations. In this study it is applied to a project in tourism sector. An investigation was made first in different companies in several sectors of activity in Portugal and has been recently successfully applied. The purpose of the chapter is to show how the identification and experimentation of concepts and methods used in classical design allow a better understanding of the implications they have in the engineering organization design theory. To renew the engineering organization design, an organizational design framework was conceived in order to use classical design methods and adapt them to organizational design theories. A contribution is made not just to the art of science of a designed-based organization design theory, but also to create and to test any organization design. Several alternative organization designs came out from the involved action research. We will present several examples of organization design interface based on real Eco Hotel. This represents a useful tool for organization design practitioners and non-organization design practitioners. For this purpose, an appliance was made and tested involving real organizations, interviews and focus groups (namely in the wine sector, or in the design sector, or yet on a NGO). The final result of this action research was a design-based organization design framework and its outcomes - which are unique, beautiful, functional, simple and sustainable – a design-based organization design interface that people love, considering always the context and user profile on which it is inserted.